Viloxazine, a Non-stimulant Norepinephrine Reuptake Inhibitor, for the Treatment of Attention Deficit Hyperactivity Disorder: A 3 Year Update - Hannah W Haddad; Paul B. Hankey; Jimin Ko; Zahaan Eswani; Pravjit Bhatti; Amber N. Edinoff; Adam M. Kaye; Alan D. Kaye (Health Psychology Research)
Attention deficit hyperactivity disorder (ADHD) is the most common neurodevelopmental disorder in childhood. Current treatment options for ADHD include pharmacological treatment (stimulants, non-stimulants, anti-depressants, anti-psychotics), psychological treatment (behavioral therapy with or without parent training, cognitive training, neurofeedback), and complementary and alternative therapies (vitamin supplementation, exercise). Central nervous system (CNS) stimulants are the primary pharmacological therapy used in treatment; however, these stimulant drugs carry a high potential for abuse and severe psychological/physical dependence. Viloxazine, a non-stimulant medication without evidence of drug dependence, is a selective norepinephrine reuptake inhibitor that has historically been prescribed as an anti-depressant medication. The extended-release (ER) form was approved by the US Food and Drug Administration (FDA) in April 2021 for the treatment of ADHD in pediatric patients aged 6-17 years. Phase 2 and 3 randomized control trials have demonstrated significant efficacy of viloxazine in improving ADHD symptoms versus placebo. Related to its long-standing use as an antidepressant, the safety profile and pharmacokinetics of viloxazine are well understood. Viloxazine appears to be a suitable alternative to current standard-of-care pharmacotherapy for ADHD, but the further investigation remains to be done in comparing its efficacy to that of current treatments.